Exploring the potential of biologically active phenolic acids from marine natural products as anticancer agents targeting the epidermal growth factor receptor - Roney, Miah; Issahaku, Abdul Rashid; Huq, A. K. M. Moyeenul; Soliman, Mahmoud E. S.; Saiful Nizam, Tajuddin; Mohd Fadhlizil Fasihi, Mohd Aluwi (Taylor & Francis, 2023)
The epidermal growth factor receptor (EGFR) dimerizes upon ligand bindings to the extracellular domain that initiates the downstream signaling cascades and activates intracellular kinase domain. Thus, activation of autophosphorylation through kinase domain results in metastasis, cell proliferation, and angiogenesis. The main objective of this research is to discover more promising anti-cancer lead compound against EGRF from the phenolic acids of marine natural products using in-silico approaches. Phenolic compounds reported from marine sources are reviewed from previous literatures. Furthermore, molecular docking was carried out using the online tool CB-Dock. The molecules with good docking and binding energies scores were subjected to ADME, toxicity and drug-likeness analysis. Subsequently, molecules from the docking experiments were also evaluated using the acute toxicity and MD simulation studies. Fourteen phenolic compounds from the reported literatures were reviewed based on the findings, isolation, characterized and applications. Molecular docking studies proved that the phenolic acids have good binding fitting by forming hydrogen bonds with amino acid residues at the binding site of EGFR. Chlorogenic acid, Chicoric acid and Rosmarinic acid showed the best binding energies score and forming hydrogen bonds with amino acid residues compare to the reference drug Erlotinib. Among these compounds, Rosmarinic acid showed the good pharmacokinetics profiles as well as acute toxicity profile. The MD simulation study further revealed that the lead complex is stable and could be future drug to treat the cancer disease. Furthermore, in a wet lab environment, both in-vitro and in-vivo testing will be employed to validate the existing computational results.